Why help others? Insights from rodent to human early childhood research - Chen, Ya-Qin; Han, Shu; Yin, Bin (Frontiers in Behavioral Neuroscience, 2023)
Helping behavior are actions aiming at assisting another individual in need or to relieve their distress. The occurrence of this behavior not only depends on automated physiological mechanisms, such as imitation or emotional contagion, that is, the individual's emotion and physiological state matching with others, but also needs motivation to sustain. From a comparative and developmental perspective, we discover that the motivation for helping behavior has a deep foundation both phylogenetically and ontogenetically. For example, empathic concern for others, relieving personal distress and the desire for social contact are universal motivations across rodents, non-human primates and human early childhood. Therefore, a circle-layered model integrating evidences for motivation for helping behavior from rodent to human early childhood research is proposed: the inner circle contains the emotional-behavioral system and the outer circle contains the affective-cognitive system. The application of this model has significance for both behavioral neuroscience research and cultivating prosocial behavior in human society.